PENGARUH EDUKASI TERHADAP PENGETAHUAN IBU DAN SIKAP TENTANG PERSIAPAN MENGHADAPI PERIMENOPAUSE DI LAPAS PEREMPUAN - Helda Febrina Dewi Andeska; Sarmauli Franshisca Sihombing (Universitas Batam, 2026)
Lack of knowledge and readiness of women in facing perimenopause, especially in confined environments such as correctional institutions, is a significant anxiety trigger, so educational interventions are needed to improve understanding and form positive attitudes in welcoming this transition phase. The purpose of this study was to determine the Effect of Education on Mothers' Knowledge and Attitudes About Preparing to Face Perimenopause. Research method This study is a quantitative study with a pre- experimental design, conducted in the class IIB Batam women's prison in 2025 with a sample of 75 respondents selected using the Slovin formula, using bivariate analysis through the Independent T-Test if the data is normally distributed and the Wilcoxon test or Mann–Whitney U Test if the data is not normally distributed, with the provision that Ha is accepted if the p-value ≤ 0.05. Results and conclusions This study shows that Asymp. Sig. 2-tailed 0.001 which is smaller than α = 0.05, indicating that there is a significant difference between maternal knowledge and an increase in attitudes after being given education Keywords : Education, Knowledge, Attitude, Perimenopause, Prison, Women